Experimental supporting data on seasonal dynamics of different soil nitrogen pools affected by long-term fertilization regimes - Ma, Qiang; Li, Shuailin; Xu, Zhiqiang; Fan, Shaobo; Xia, Zhuqing; Zhou, Changrui; Zhu, Mengmeng; Yu, Wantai (Data in brief, 2020)
The data presented in this article are related to the research paper entitled “Changes in N supply pathways under different long-term fertilization regimes in Northeast China” [1]. Seasonal dynamics of soil NH4+–N, NO3−–N, soil microbial biomass nitrogen (N) and fixed NH4+ were provided on the basis of a 26-year long-term experiment, including six treatments: no fertilizer (CK), recycled manure (M), N and P fertilizers (NP), P and K fertilizers (PK), N, P and K fertilizers (NPK), and NPK fertilizers with recycled manure (NPKM). The presentation of potential N retention and supply through soil microbial biomass N and fixed NH4+ pools at different growth stages is helpful for comparing the effects of different N pools on soil N transformation and assessing synchronies between crop N demand and soil N supply through different N pools.